A cross-sectional quantitative analysis of the natural history of free sialic acid storage disease: an ultra-orphan multisystemic lysosomal storage disorder - Zielonka, Matthias; Garbade, Sven; Kölker, Stefan; Hoffmann, Georg F.; Ries, Markus (Genetics in medicine, 2019)
Quantitative definition of the natural history of free sialic acid storage disease (SASD, OMIM 604369), an orphan disorder due to the deficiency of the proton-driven carrier SLC17A5. Analysis of published cases with SASD (N = 116) respecting STROBE criteria. Main outcome parameters: survival and diagnostic delay. Phenotype, phenotype-biomarker associations, and geographical patient distribution were explored. Median age at disease onset was 0.17 years. Median age at diagnosis was 3 years with a median diagnostic delay of 2.5 years. Median survival was 11 years. The biochemical phenotype clearly predicted the disease course: patients with a urinary free sialic acid excretion below 6.37-fold or an intracellular free sialic acid storage in fibroblasts below 7.37-fold of the mean of normal survived longer than patients with biochemical values above these thresholds. Cluster analysis of disease features suggested a continuous phenotypic spectrum. Patient distribution was panethnic. Combination of neurologic symptoms, visceromegaly, and dysmorphic features and/or nonimmune hydrops fetalis should prompt specific tests for SASD, reducing diagnostic delay. The present quantitative data inform clinical studies and may stimulate and accelerate development of specific therapies. Biomarker-phenotype association is particularly important for both counseling parents and study design.
Published: 06 June 2018
Gesehen am 17.04.2019